A Three-Phase Symmetrical DC-Link Multilevel Inverter with Reduced Number of DC Sources - Hasan, M.; Abu-Siada, Ahmed; Dahidah, M. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
This paper presents a novel three-phase DC-link multilevel inverter topology with reduced number of input DC power supplies. The proposed inverter consists of series-connected half-bridge modules to generate the multilevel waveform and a simple H-bridge module, acting as a polarity generator. The inverter output voltage is transferred to the load through a three-phase transformer, which facilitates a galvanic isolation between the inverter and the load. The proposed topology features many advantages when compared with the conventional multilevel inverters proposed in the literatures. These features include scalability, simple control, reduced number of DC voltage sources and less devices count. A simple sinusoidal pulse-width modulation technique is employed to control the proposed inverter. The performance of the inverter is evaluated under different loading conditions and a comparison with some existing topologies is also presented. The feasibility and effectiveness of the proposed inverter are confirmed through simulation and experimental studies using a scaled down low-voltage laboratory prototype.